Comparison of mini-percutaneous nephrolithotomy and standard percutaneous nephrolithotomy in the treatment of renal calculi with renal insufficiency - Weiyang Wei; Chuanpeng Zhou; Hao Yang; Qi Wang; Hongxing Huang; Yaqiang Huang (Scientific Reports)
Abstract To compare the clinical efficacy and safety of mini-percutaneous nephrolithotomy (MPCNL) and standard percutaneous nephrolithotomy (SPCNL) in the treatment of kidney stones combine with renal insufficiency. The data of 320 patients with renal calculi and an eGFR < 60 mL/min/1.73m2 who underwent percutaneous nephrolithotomy (PCNL) at Zhongshan City People’s Hospital from January 2018 to June 2023 were retrospectively analyzed; 164 patients were treated with MPCNL, and 156 were treated with SPCNL. The clinical efficacy of the MPCNL and SPCNL regimens was compared in terms of stone-free rate (SFR), renal function change, hemoglobin (HGB) drop and other complication rates (complications were classified by using the Clavien‒Dindo system). The SFR was 67.1% in the MPCNL group and 67.9% in the SPCNL group (P = 0.867). The overall eGFR of the two groups was significantly improved at 1 month after the operation (P < 0.001). Postoperative renal function was stable, improved and worse in 50.0% (n = 82) vs. 53.8% (n = 84), 39.0% (n = 64) vs. 42.4% (n = 66) and 11.0% (n = 18) vs. 3.8% (n = 6) of the MPCNL and SPCNL patients, respectively, compared with preoperative renal function (P = 0.053). In addition, the overall postoperative complication rates between the two groups was not significantly different (P = 0.103). Patients who underwent MPCNL had a lower transfusion rate (7.9% vs. 16.7%, P = 0.017) and shorter hospital stay (4.57 ± 3.14 vs. 7.16 ± 4.05 days, P < 0.001) than those in the SPCNL group. MPCNL and SPCNL have positive effects on the treatment of renal calculi in patients with renal insufficiency; both have acceptable SFRs and complication rates, stable or improved renal function in most patients.